2015
DOI: 10.1542/peds.2014-2141
|View full text |Cite
|
Sign up to set email alerts
|

Anaerobic Antimicrobial Therapy After Necrotizing Enterocolitis in VLBW Infants

Abstract: OBJECTIVE: To evaluate the effect of anaerobic antimicrobial therapy for necrotizing enterocolitis (NEC) on clinical outcomes in very low birth weight (≤1500 g) infants. METHODS: We identified very low birth weight infants with NEC from 348 US NICUs from 1997 to 2012. Anaerobic antimicrobial therapy was defined by antibiotic exposure on the first day of NEC. We matched (1:1) infants exposed to anaerobic antimicrobial therapy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
45
0
2

Year Published

2016
2016
2018
2018

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(47 citation statements)
references
References 42 publications
0
45
0
2
Order By: Relevance
“…We excluded several studies from our meta-analysis due to overlapping study populations 2 12–16. Some studies17–25 showed partially overlapping study populations with Autmizguine et al ,26 however described different GI outcomes. Thyoka et al published two studies with a largely overlapping study population, but reported different outcomes 27 28.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…We excluded several studies from our meta-analysis due to overlapping study populations 2 12–16. Some studies17–25 showed partially overlapping study populations with Autmizguine et al ,26 however described different GI outcomes. Thyoka et al published two studies with a largely overlapping study population, but reported different outcomes 27 28.…”
Section: Resultsmentioning
confidence: 99%
“…Thyoka et al published two studies with a largely overlapping study population, but reported different outcomes 27 28. The studies of Hall et al /Thyoka et al 28 29 and Autmizguine et al /O’Connor and Sawin18 26 showed only a small partial overlap and provided mostly unique information. Therefore, we included all four studies (see online supplementary appendix D).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…-Gram-negatives and anaerobes) plus or minus the administration of an anti-fungal agent is accepted. Autmizguine et al (18) showed that administration of an anaerobic antimicrobial medication resulted in increased incidence of stricture formation, possibly due to the reduced mortality when compared to the control group. There was no difference in death between the exposed and non-exposed groups.…”
Section: Medical Managementmentioning
confidence: 99%